If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1-2m=-6m-3
We move all terms to the left:
1-2m-(-6m-3)=0
We get rid of parentheses
-2m+6m+3+1=0
We add all the numbers together, and all the variables
4m+4=0
We move all terms containing m to the left, all other terms to the right
4m=-4
m=-4/4
m=-1
| 8x+14∘=6x+34∘ | | w÷(-4)=-0.9 | | 1-((x-5)/3)=((x+2)/5)-((6x-1)/15) | | 3x-7=2(x+4)+x-1 | | 19-6p=-41 | | 79-(-5x-6)0=245x+336 | | 22-2f=6 | | 3(x+1)=2x+4+x-1 | | 2q-8q+9=-8q-9 | | 4v=-68 | | -3(x-1)=-(2x-2)-x+1 | | -6u=-7-7u | | 62+94=77x+70-40x | | -9+2+p=5-p | | -155=-5(1+6a) | | Y=1/11x+9 | | 24=-8b+2b | | w+1.7=9.13 | | 3(6x-3)=10x+7 | | 2y+3(y+5)=6y | | 7x+0.8=7.8 | | 10-12(1-x)=8(-12-6x)-14 | | F=3x-0,5 | | -7m+10=-5m-10 | | 3x-7-2x=2x-4x+4 | | 7s=8s-10 | | F=3x-½ | | 3a-a+23=-13 | | 2x+8=185 | | -4+8c=9c | | -175=-5(7+4a) | | -d-10=8+5d |